Composition, molded article, and method for producing same
Patent Information
- Application Number
- JP2022163030
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-10-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2038-02-26
AI Technical Summary
【0010】 本発明によれば、方向性によらず高い機械特性を有する組成物が提供される。
Smart Images

Figure 0007608679000001 
Figure 0007608679000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition, a molded article, and a method for producing the same. [Background technology]
[0002] In recent years, cellulose fibers have been attracting attention due to their light weight and high strength, and compositions in which cellulose fibers are added to resins have been studied. Compositions in which cellulose fibers are added to resins exhibit high mechanical properties.
[0003] For example, Patent Document 1 describes an invention relating to a fiber-containing resin composition containing cellulose fibers and an olefin resin, in which the cellulose constituting the cellulose fibers is characterized by having a functional group with a linear or branched aliphatic hydrocarbon chain having 5 or more carbon atoms.
[0004] Patent Document 1 describes that cellulose fibers are difficult to disperse in resin because they are hydrophilic, that various improvements have been made to disperse cellulose fibers in resin, and that by using cellulose fibers having functional groups with linear or branched aliphatic hydrocarbon chains having 5 or more carbon atoms, it is possible to significantly increase mechanical properties while suppressing the decrease in transparency caused by the incorporation of cellulose fibers. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-15512 A Summary of the Invention [Problem to be solved by the invention]
[0006] According to the fiber-containing resin composition described in Patent Document 1, high mechanical properties can be obtained by adding cellulose fibers to an olefin resin. However, it has been found that since cellulose fibers tend to be aligned in the same direction, the mechanical properties are anisotropic, and while the mechanical properties are high in one direction, the mechanical properties may be insufficient in another direction.
[0007] Therefore, an object of the present invention is to provide a composition having high mechanical properties regardless of directionality. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by using cellulose fibers having a specific aspect ratio in combination with a filler having a specific aspect ratio, thereby completing the present invention.
[0009] That is, the present invention relates to a composition comprising a thermoplastic resin, cellulose fibers having an aspect ratio of 30 or more, and a filler having an aspect ratio of 10 or more. Effect of the Invention
[0010] According to the present invention, a composition is provided which has high mechanical properties regardless of directionality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described in detail.
[0012] <Composition> The composition includes a thermoplastic resin, cellulosic fibers having an aspect ratio of 30 or greater, and a filler having an aspect ratio of 10 or greater.
[0013] In a conventional composition containing a thermoplastic resin and cellulose fibers, in order to obtain mechanical properties, it is necessary to disperse the cellulose fibers in the thermoplastic resin. In this case, most of the cellulose fibers are usually oriented in approximately the same direction. For example, when the composition is produced by kneading, the cellulose fibers are oriented along the flow direction of the resin (MD). This allows high mechanical properties (elastic modulus, strength, etc.) to be realized in the MD direction. However, in the direction perpendicular to the flow of the resin (TD direction), sufficient mechanical properties may not be realized. As a result, the obtained molded product may not have sufficient mechanical properties depending on its directionality.
[0014] In contrast, in the composition according to the present embodiment, the cellulose fibers are oriented in approximately the same direction (e.g., aligned along the MD direction), and the filler used in combination is oriented in a direction approximately perpendicular to the cellulose fibers (e.g., aligned along the TD direction). As a result, a composition having high mechanical properties can be obtained regardless of the directionality.
[0015] [Thermoplastic resin] By thermoplastic resin is meant a resin that softens at its glass transition temperature (Tg) or melting point.
[0016] Examples of thermoplastic resins include, but are not limited to, polyethylene (PE) resins (high density polyethylene (HDPE), low density polyethylene (LDPE), very low density polyethylene (VLDPE), linear low density polyethylene (LLDPE), ultra-high molecular weight polyethylene (UHMW-PE), maleic anhydride modified polyethylene, etc.), polypropylene (PP) resins, polyvinyl chloride (PVC) resins (polyvinylidene chloride, etc.), polystyrene (PS) resins (polystyrene, rubber modified polystyrene resin, etc.), polyvinyl acetate (PVAc) resins, polyurethane (PU) resins, acrylonitrile-butadiene-styrene (ABS) resins, acrylonitrile-styrene (AS) resins, acrylic resins (polymethyl methacrylate resin (PMMA)), polyamide resins (nylon, etc.), polyacetal resins, etc.), and the like. Examples of the thermoplastic resin include polycarbonate resin, polyester resin (polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), etc.), polycarbonate (PC) resin, cyclic polyolefin resin, cellulose acetate propionate (CAP) resin, diacetyl cellulose (DAC) resin, polyphenylene sulfide (PPS) resin, polytetrafluoroethylene (PTFE) resin, polysulfone (PSF) resin, polyethersulfone (PES) resin, polyetheretherketone (PEEK) resin, polyimide (PI) resin, polyamideimide (PAI) resin, polyetherimide (PEI) resin, polyketone resin, etc. These thermoplastic resins may be used alone or in combination of two or more.
[0017] Of the above, it is preferable to use polyethylene (PE) resin, polypropylene (PP) resin, polyester resin, polyamide resin, or polycarbonate (PC) resin, and it is more preferable to use polyethylene (PE) resin, polypropylene (PP) resin, or polyamide resin.
[0018] The content of the thermoplastic resin is preferably 50 to 99% by mass, more preferably 60 to 95% by mass, based on the total mass of the thermoplastic resin, the cellulose fiber, and the filler. If the content of the thermoplastic resin is 50% by mass or more, it is preferable because it can be molded into various shapes by heating and melting. On the other hand, if the content of the thermoplastic resin is 99% by mass or less, it is preferable because it can be given various functions by reinforcing the resin.
[0019] [Cellulose fiber] Cellulose fibers are materials in which cellulose has a fibrous shape. The cellulose fibers are oriented in the resin generally along the flow direction of the resin (MD direction, etc.), and thus have the function of imparting high mechanical properties in that direction. In this specification, the term "cellulose fibers" refers to fibrous cellulose fibers having a width of 1000 μm or less.
[0020] As described above, the width of the cellulose fiber is 1000 μm or less, preferably 100 μm or less, more preferably 4 nm to 50 μm, and even more preferably 4 nm to 25 μm. When the width of the cellulose fiber is 1000 μm or less, it is preferable because the composite effect appears and the reinforcing effect can be increased. In this specification, the "width of the cellulose fiber" is a value measured by the following method. That is, the cellulose fiber is observed with a scanning electron microscope (SEM) (magnification: 5000 times), and a straight line in which 20 or more cellulose fibers intersect in one field of view is provided. Then, for all the cellulose fibers intersecting on the straight line, the distance between the two points with the smallest numerical value in the observation screen is measured, and the average value is taken as the width of the cellulose fiber. In addition, the width of the cellulose fiber present in the composition is measured using a measuring cellulose fiber prepared by the following method. That is, first, a sample of the composition of 1 cm x 1 cm x 0.1 mm is prepared. Next, the sample is immersed in an extraction solvent to extract the thermoplastic resin of the sample. At that time, it may be heated and boiled. The remaining cellulose fibers are then dried to obtain cellulose fibers for measurement. The extraction solvent used to extract the thermoplastic resin varies depending on the thermoplastic resin used. For example, when the thermoplastic resin is high density polyethylene (HDPE), polypropylene, etc., xylene is used as the extraction solvent. When the thermoplastic resin is polyamide, polyester, etc., o-chlorophenol is used as the extraction solvent.
[0021] The fiber length of the cellulose fibers is preferably 100 nm or more, more preferably 500 nm to 10,000 μm, and even more preferably 1 to 1,000 μm. When the fiber length of the cellulose fibers is 100 nm or more, it is preferable because the reinforcing effect can be increased by the composite effect. In this specification, the "fiber length of the cellulose fibers" is a value measured by the following method. That is, the cellulose fibers are observed with a scanning electron microscope (SEM) (magnification: 1,000 times), 25 fields of view are synthesized, 20 cellulose fibers in which the start point and the end point are observed are selected, and the distance between the two points with the largest value is measured, and the average value is taken as the fiber length of the cellulose fibers. In addition, for the measurement of the fiber length of the cellulose fibers present in the composition, cellulose fibers for measurement obtained by the same method as the measurement of the width of the cellulose fibers described above are used.
[0022] The aspect ratio of the cellulose fibers is 30 or more, preferably 50 or more, more preferably 50 to 20,000, and even more preferably 100 to 2,000. When the aspect ratio of the cellulose fibers is 30 or more, the cellulose fibers are likely to be oriented in the same direction (e.g., MD direction) in the thermoplastic resin, and high mechanical properties can be obtained particularly in the oriented direction, which is preferable. In this specification, the "aspect ratio" refers to the fiber length of the cellulose fibers relative to the width of the cellulose fibers (fiber length of the cellulose fibers / width of the cellulose fibers).
[0023] The cellulose fiber is not particularly limited, and any known cellulose fiber may be used.
[0024] In one embodiment, the cellulose fibers include pulp and synthetic fibers, and defibrated versions of these (defibrated materials). The "cellulose fiber width" of pulp and synthetic fibers is usually 10 to 50 μm, preferably 20 to 30 μm. The "cellulose fiber width" of the defibrated materials is usually less than 10 μm, preferably 50 nm to 5 μm.
[0025] Examples of the pulp include wood pulp such as coniferous pulp made from fir, pine, etc., and hardwood pulp made from eucalyptus, poplar, etc.; non-wood pulp such as straw pulp, kenaf pulp, bagasse pulp, bamboo pulp, reed pulp, mulberry pulp, and cotton linter pulp; and waste paper pulp obtained by deinking waste paper, etc.
[0026] Examples of the synthetic fibers include rayon, polynosic, cupra, lyocell, and cellophane.
[0027] In this case, the pulp and the synthetic fibers may be bleached (bleached pulp, etc.), or may not be bleached (unbleached pulp, etc.).
[0028] Of the above-mentioned pulps and synthetic fibers, pulp is preferred, wood pulp is more preferred, unbleached softwood kraft pulp (NUKP), oxygen bleached softwood kraft pulp (NOKP), bleached softwood kraft pulp (NBKP), bleached hardwood kraft pulp (LBKP), unbleached hardwood kraft pulp (LUKP), or oxygen bleached hardwood kraft pulp (LOKP) is even more preferred, and unbleached softwood kraft pulp (NUKP), oxygen bleached softwood kraft pulp (NOKP), or bleached softwood kraft pulp (NBKP) is particularly preferred.
[0029] The defibrated material is not particularly limited, and examples thereof include cellulose microfibrils, cellulose nanofibers (CNF), and cellulose nanocrystals (CNC).
[0030] The defibration to obtain the defibrated material may be performed by mechanical treatment, chemical treatment, or a combination of these. Methods for obtaining the defibrated material by mechanical treatment include the high-pressure homogenizer method, the underwater head-on collision method, the grinder method, and the ball mill method. Methods for obtaining the defibrated material by chemical treatment include the TEMPO catalytic oxidation method. Furthermore, defibration may be performed by utilizing the force applied when producing the composition (for example, when melt-kneading). These defibration methods may be applied alone or in combination of two or more types.
[0031] The cellulose fibers may also contain hemicellulose, lignin, and the like.
[0032] The hemicellulose content is preferably 10% by mass or less, and more preferably 5% by mass or less, based on the total mass of the cellulose fibers. In this specification, the "hemicellulose content" is calculated using a value measured by detergent analysis.
[0033] The lignin content is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 5% by mass or less, based on the total mass of the cellulose fibers. In this specification, the "lignin content" is calculated using a value measured by the Klason method.
[0034] The above-mentioned cellulose fibers may be unmodified or may be modified.
[0035] The term "cellulose fiber is modified" means that at least one of the hydroxyl groups (-OH) at the C2, C3, and C6 positions of the β-glucose molecules constituting the cellulose is modified with an acyl group (-COR) to form an ester bond (-OCOR). In this case, the acyl group may be substituted evenly at the C2, C3, and C6 positions of the β-glucose unit, or may be substituted with a distribution.
[0036] The R is not particularly limited, but examples thereof include a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 20 carbon atoms, a substituted or unsubstituted alkyl group having 2 to 20 carbon atoms, and a substituted or unsubstituted aromatic group having 6 to 20 carbon atoms.
[0037] Examples of the alkyl group having 1 to 20 carbon atoms include, but are not limited to, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2,2-dimethylpropyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a pentadecyl group, a hexadecyl group, a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, and a cyclodecyl group.
[0038] The alkenyl group having 2 to 20 carbon atoms is not particularly limited, and examples thereof include a vinyl group, an allyl group, a propenyl group, an isopropenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, a 1-hexenyl group, a 2-hexenyl group, a 3-hexenyl group, a 4-hexenyl group, a 5-hexenyl group, a cyclopentenyl group, a cyclohexenyl group, a cyclooctenyl group, and a 1-methyl-2-propyl-3-hexenyl group.
[0039] The alkynyl group having 2 to 20 carbon atoms is not particularly limited, but examples thereof include an ethynyl group, a 2-propynyl group, and a 2-butynyl group.
[0040] The alkyl group having 1 to 20 carbon atoms, the alkenyl group having 2 to 20 carbon atoms, and the alkynyl group having 2 to 20 carbon atoms may have a substituent. Examples of the substituent include a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), a hydroxy group, a carboxy group, an amino group, an alkylamino group (-NHR'2), a dialkylamino group (-NR'2), a trialkylammonium group (-NR'3), and the like. +), a nitro group, a thiol group, etc. In this case, R' may be an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or an alkynyl group having 2 to 10 carbon atoms. These substituents may be present alone or in combination of two or more.
[0041] The aromatic group having 6 to 20 carbon atoms is not particularly limited, and examples thereof include a phenyl group, a naphthyl group, an anthracenyl group, a pentalenyl group, an indenyl group, an indacenyl group, a biphenylenyl group, an acenaphthylenyl group, a phenalenyl group, a pyrrolyl group, a furyl group, a thienyl group, an imidazolyl group, an imidazolidinyl group, a pyrazolyl group, a pyrazolidinyl group, a thiazolyl group, a thiazolidinyl group, an isothiazolyl group, an isothiazolidinyl group, an oxazol ... Examples of such an alkyl group include a zolyl group, an oxazolidinyl group, an isoxazolyl group, an isoxazolidinyl group, a furazanyl group, a benzofuranyl group, an isobenzofuranyl group, a pyridyl group, a pyrazinyl group, a pyrimidinyl group, a pyridazinyl group, a quinolyl group, a carbazolyl group, a phenanthridinyl group, an acridinyl group, a perimidinyl group, a phenanthrolinyl group, a phenazinyl group, a phenothiazinyl group, a phenoxazinyl group, and an anthyridinyl group.
[0042] The substituent of the aromatic group having 6 to 20 carbon atoms is not particularly limited, and examples thereof include an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), a hydroxy group, a carboxy group, an amino group, an alkylamino group (-NHR'2), a dialkylamino group (-NR'2), a trialkylammonium group (-NR'3), + ), a nitro group, a thiol group, etc. These substituents may be present alone or in combination of two or more.
[0043] Of the above, R is preferably a methyl group, a 1-carboxymethyl-2-propyl-3-hexenyl group, a 2-carboxy-3-propyl-4-heptenyl group, a 1-carboxymethyl-3-tridekenyl group, a 2-carboxy-4-tetradekenyl group, a 1-carboxymethyl-2-heptadekenyl group, or a 2-carboxy-3-octadekenyl group.
[0044] When the cellulose fibers are modified, if the cellulose fibers contain hemicellulose and lignin, at least one of the hydroxyl groups in the hemicellulose and lignin may be modified.
[0045] When the cellulose fiber has a plurality of the above-mentioned R, each R may be the same or different.
[0046] The above-mentioned cellulose fibers can be modified using known compounds. For example, when R is a methyl group (when the hydroxyl group of the cellulose fiber is modified with an acetyl group to form a methylcarbonyloxy group (-OCOCH3)), the cellulose fibers can be modified using acetic acid, acetic anhydride, or the like. When R is an alkenyl group, the cellulose fibers can be modified using an alkenyl carboxylic acid. Furthermore, when R is an alkenyl group having a carboxyl group as a substituent, the cellulose fibers can be modified using an alkenyl succinic anhydride, an alkenyl dicarboxylic acid, or the like.
[0047] When the cellulose fibers are modified, the degree of substitution is preferably 0.05 to 2.0, more preferably 0.1 to 1.0, and even more preferably 0.1 to 0.8. A degree of substitution of 0.05 or more is preferable because the cellulose fibers can be suitably dispersed in the resin. On the other hand, a degree of substitution of 2.0 or less is preferable because the strength of the cellulose fibers is maintained and high mechanical properties can be achieved. In this specification, the "degree of substitution" refers to the average degree of substitution of hydroxyl groups per β-glucose unit, and is calculated by the following formula.
[0048] Substitution degree=3-DS In this case, "DS" means the number of hydroxyl groups per β-glucose unit and can be measured by the following formula.
[0049] DS=0.0113X-0.0122 In the above formula, X is the 1733 cm in the infrared absorption spectrum measured by infrared spectroscopy (IR) using a Fourier transform infrared spectrophotometer (FT-IR). -1 The DS is the absorption peak area of the carbonyl (C=O) of the ester group nearby. Since the DS can be measured sequentially during the cellulose modification reaction, it can be used to track the reaction.
[0050] As a specific example, when the hydroxyl groups at the C2, C3, and C6 positions of β-glucose are all substituted with acyl groups, the degree of substitution (maximum value) is 3.0.
[0051] Of the above, the cellulose fibers are preferably unmodified cellulose or partially modified cellulose (with a degree of substitution of 2 or less, preferably 0.1 to 1).
[0052] The above-mentioned cellulose fibers may be used alone or in combination of two or more kinds.
[0053] The content of the cellulose fiber is preferably 0.1 to 20% by mass, more preferably 0.1 to 10% by mass, and even more preferably 0.5 to 10% by mass, based on the total mass of the thermoplastic resin, the cellulose fiber, and the filler. If the content of the cellulose fiber is 0.1% by mass or more, it is preferable because high mechanical properties, particularly high physical properties (elastic modulus, strength) in the flow direction of the resin (MD direction), can be obtained. On the other hand, if the content of the cellulose fiber is 20% by mass or less, it is preferable because the melt viscosity can be reduced and handling is excellent.
[0054] [Filler] A filler is an additive that is added to a resin and has the function of imparting high mechanical properties in a direction (such as the TD direction) that is approximately perpendicular to the flow direction of the resin in the resin.
[0055] The aspect ratio of the filler is 10 or more, preferably 10 to 75, more preferably 10 to 60, and even more preferably 20 to 50. When the aspect ratio of the filler is 10 or more, high mechanical properties are obtained, and the mechanical properties (elastic modulus, strength, etc.) tend to be further increased, which is preferable. In addition, when the aspect ratio of the filler is 75 or less, anisotropy in the elastic modulus is less likely to occur, which is preferable. In addition, in this specification, "aspect ratio of the filler" means the maximum diameter of the filler relative to the minimum diameter of the filler (maximum diameter of the filler / minimum diameter of the filler). Here, "maximum diameter of the filler" is the maximum length when the filler is sandwiched between a pair of parallel surfaces. Similarly, "minimum diameter of the filler" is the minimum length when the filler is sandwiched between a pair of parallel surfaces. In addition, when the filler is flat, "minimum diameter of the filler" corresponds to the so-called thickness. The "maximum diameter of the filler" is measured by observing the filler with a scanning electron microscope (SEM) (magnification: 5,000 times), randomly selecting 30 fillers present in one field of view, and measuring the maximum diameter. The "minimum diameter of the filler" is measured by similarly observing the filler with a SEM (magnification: 10,000 times), randomly selecting 30 fillers present in four fields of view, and measuring the minimum diameter. The maximum diameter and minimum diameter of the filler present in the composition are measured at 25°C using a sample of the composition measuring 1 cm x 1 cm x 0.1 mm.
[0056] The maximum diameter of the filler is preferably 50 μm or less, more preferably 30 μm or less, even more preferably 10 μm or less, particularly preferably 0.01 to 10 μm, extremely preferably 0.1 to 10 μm, and most preferably 1 to 7.5 μm. If the maximum diameter of the filler is 50 μm or less, the volume effect as an additive is fully exerted, and as a result, mechanical properties (elastic modulus, strength, etc.) can be improved, which is preferable.
[0057] The minimum diameter of the filler is preferably 0.001 μm or more, more preferably 0.01 μm or more, further preferably 0.05 to 5 μm, and particularly preferably 0.05 to 0.75 μm. If the minimum diameter of the filler is 0.001 μm or more, the aspect ratio of the filler becomes high, and the mechanical properties of the composite material can be improved, which is preferable.
[0058] The filler is not particularly limited, and either an organic filler or an inorganic filler can be used.
[0059] The organic filler is not particularly limited, but examples thereof include resin particles such as (meth)acrylic resin particles, silicone resin particles, styrene resin particles, and urethane resin particles; and organic fibers such as aramid fibers.
[0060] The inorganic filler is not particularly limited, but examples thereof include metal compounds, silicate minerals, carbon compounds, inorganic fibers, and the like.
[0061] The metal oxide is not particularly limited, but examples thereof include aluminum oxide, silicon oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, calcium carbonate, barium carbonate, magnesium carbonate, barium sulfate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, aluminum nitride, boron nitride, and magnesium chloride.
[0062] The silicate minerals are not particularly limited, and include nesosilicate minerals (island stripe tetrahedral silicate minerals) such as olivine, garnet, zircon, sillimanite, and kyanite; sorosilicate minerals (group structure silicate minerals) such as gehlenite, lawsonite, and calcite; cyclosilicate minerals (ring-shaped silicate minerals) such as beryl, cordierite, and osumilite; enstatite, ferrozonite, pigeonite, diopside, jadeite, and wollastonite. Examples of inosilicate minerals include anthophyllite, cumingtonite, grunerite, tremolite, etc. (ring-type silicate minerals); phyllosilicate minerals (layered silicate minerals) such as kaolinite, halloyite, montmorillonite, hectorite, talc, mica, chlorite, vermiculite, etc.; and tectosilicate minerals (network structure silicate minerals) such as orthoclase, albite, anorthite, nepheline, zeolite, etc.
[0063] The carbon compound is not particularly limited, but examples thereof include graphite, carbon nanotubes, carbon nanohawks, carbon black (soft carbon, hard carbon), and carbon nanofibers.
[0064] The inorganic fibers are not particularly limited, but examples thereof include glass fibers, carbon fibers, and boron fibers.
[0065] Of the above, the filler is preferably an inorganic filler, more preferably a silicate mineral or a carbon compound, even more preferably a phyllosilicate mineral, a tectosilicate mineral or a carbon compound, and even more preferably talc, mica, scumetite, graphite or graphene.
[0066] The above-mentioned fillers may also be surface-modified.
[0067] The surface treatment agent used for the surface modification is not particularly limited, but examples thereof include epoxysilane, aminosilane, (meth)acrylsilane, vinylsilane, phenylsilane, mercaptosilane, and silane coupling agents.
[0068] These surface treatment agents may be used alone or in combination of two or more kinds.
[0069] The above-mentioned fillers may be used alone or in combination of two or more kinds.
[0070] The content of the filler is preferably 1 to 40% by mass, more preferably 2 to 30% by mass, and even more preferably 5 to 20% by mass, based on the total mass of the thermoplastic resin, the cellulose fiber, and the filler. If the content of the filler is 1% by mass or more, it is preferable because high mechanical properties, particularly high physical properties (elastic modulus, strength) in the direction perpendicular to the flow of the resin (TD direction), can be obtained. On the other hand, if the content of the filler is 40% by mass or less, it is preferable because the toughness of the composite material can be increased.
[0071] [Dispersant] The composition may contain a dispersant, which has the function of dispersing the cellulose fibers in the thermoplastic resin.
[0072] The dispersant is not particularly limited, but examples thereof include a hydrophilic group-containing compound containing at least one hydrophilic group selected from the group consisting of a hydroxy group, a carboxy group, a quaternary ammonium group, a phosphoric acid group, and a sulfonic acid group, and salts thereof; a glycol ether compound; a homopolymer of the hydrophilic group-containing compound or the glycol ether compound; a first copolymer containing at least one of the hydrophilic group-containing compound and the glycol ether compound, and / or a hydrophobic compound; a second copolymer of a (meth)acrylic acid alkyl ester monomer having an alkyl group with 6 to 18 carbon atoms and an acrylic monomer having an amide group, and / or other monomers; a choline compound; and the like.
[0073] The hydrophilic group-containing compound is not particularly limited, and examples thereof include hydroxy group-containing compounds such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, ethylene glycol mono(meth)acrylate, and propylene glycol mono(meth)acrylate; (meth)acrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, polyoxyethylene methyl ether carboxylic acid, and N-acyl glutamic acid. quaternary ammonium group-containing compounds such as hexadecyltrimethylammonium, myristyltrimethylammonium, benzylated dimethylaminoethyl (meth)acrylate, and [2-{(meth)acryloyloxy}ethyl]trimethylammonium; phosphate group-containing compounds such as phosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, metaphosphoric acid, trimetaphosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, and phosphonic acid; and sulfonic acid group-containing compounds such as dodecyl sulfuric acid, dodecylbenzenesulfonic acid, styrenesulfonic acid, and dimethylsulfosuccinic acid.
[0074] In this case, when the hydrophilic group-containing compound is a salt, the counter ion of the salt is not particularly limited, but when it is an anion, it is preferably a halide ion (fluoride ion, chloride ion, bromide ion, iodide ion), etc. On the other hand, when it is a cation, it is preferably an alkali metal salt (sodium salt, potassium salt, lithium salt), a salt of a Group 2 element (calcium salt, magnesium salt), etc.
[0075] The glycol ether compound is not particularly limited as long as it is other than the above-mentioned hydrophilic group-containing compounds, and examples thereof include methoxyethylene glycol (meth)acrylate, ethylethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, and phenoxyethylene glycol methacrylate.
[0076] The homopolymer is not particularly limited, but examples thereof include poly(meth)acrylic acid, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyphosphoric acid, polystyrene sulfonic acid, methoxypolyethylene glycol (meth)acrylate, ethylpolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.
[0077] The hydrophilic group-containing compound and the glycol ether compound that can be used in the first copolymer are those described above. In this case, the hydrophilic group-containing compound and the glycol ether compound may be used alone or in combination of two or more kinds.
[0078] The hydrophobic compound that can be used in the first copolymer is not particularly limited, but includes (meth)acrylic monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, capryl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, stearyl (meth)acrylate, oleyl (meth)acrylate, linoleyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and benzyl (meth)acrylate; styrene-based monomers such as styrene, methylstyrene, ethylstyrene, and dimethylstyrene. The hydrophobic compounds may be used alone or in combination of two or more.
[0079] Specific examples of the first copolymer include a copolymer of a hydroxy group-containing compound and a (meth)acrylic monomer, a copolymer of a carboxy group-containing compound and a (meth)acrylic monomer, and a copolymer of a quaternary ammonium group-containing compound and a (meth)acrylic monomer. More specifically, the copolymers include a copolymer of 2-hydroxyethyl (meth)acrylate and methyl (meth)acrylate, a copolymer of 2-hydroxyethyl (meth)acrylate and lauryl (meth)acrylate, a copolymer of 2-hydroxyethyl (meth)acrylate and cyclohexyl (meth)acrylate, a copolymer of 2-hydroxyethyl (meth)acrylate and t-butylcyclohexyl (meth)acrylate, a copolymer of 2-hydroxyethyl (meth)acrylate and isobornyl (meth)acrylate, a copolymer of 2-hydroxyethyl (meth)acrylate and (meth)acrylic acid, a copolymer of 2-hydroxyethyl (meth)acrylate and dicyclopentenyloxyethyl (meth)acrylate, a copolymer of (meth)acrylic acid and methyl (meth)acrylate, a copolymer of (meth)acrylic acid and lauryl (meth)acrylate, a copolymer of (meth)acrylic acid and cyclohexyl (meth)acrylate, a copolymer of (meth)acrylic acid and Copolymers with t-butylcyclohexyl (meth)acrylate, copolymers of (meth)acrylic acid and isobornyl (meth)acrylate, copolymers of (meth)acrylic acid and (meth)acrylic acid, copolymers of (meth)acrylic acid and dicyclopentenyloxyethyl (meth)acrylate, copolymers of benzylated dimethylaminoethyl (meth)acrylate and methyl (meth)acrylate, copolymers of benzylated dimethylaminoethyl (meth)acrylate and lauryl (meth)acrylate, copolymers of benzylated dimethylaminoethyl (meth)acrylate and cyclohexyl (meth)acrylate, copolymers of benzylated dimethylaminoethyl (meth)acrylate and t-butylcyclohexyl (meth)acrylate, copolymers of benzylated dimethylaminoethyl (meth)acrylate and isobornyl (meth)acrylate, copolymers of benzylated dimethylaminoethyl (meth)acrylate and (meth)acrylic acid,Examples of such copolymers include a copolymer of a benzylated product of dimethylaminoethyl (meth)acrylate and dicyclopentenyloxyethyl (meth)acrylate, a copolymer of [2-{(meth)acryloyloxy}ethyl]trimethylammonium and methyl (meth)acrylate, a copolymer of [2-{(meth)acryloyloxy}ethyl]trimethylammonium and lauryl (meth)acrylate, a copolymer of [2-{(meth)acryloyloxy}ethyl]trimethylammonium and cyclohexyl (meth)acrylate, a copolymer of [2-{(meth)acryloyloxy}ethyl]trimethylammonium and t-butylcyclohexyl (meth)acrylate, a copolymer of [2-{(meth)acryloyloxy}ethyl]trimethylammonium and isobornyl (meth)acrylate, a copolymer of [2-{(meth)acryloyloxy}ethyl]trimethylammonium and (meth)acrylic acid, and a copolymer of [2-{(meth)acryloyloxy}ethyl]trimethylammonium and dicyclopentenyloxyethyl (meth)acrylate. In this case, the copolymer may be any of a random copolymer, an alternating copolymer, a block copolymer, and a graft copolymer, but is preferably a random copolymer or a block copolymer. The hydrophobic compound can be incorporated into the dispersant by copolymerization to increase the hydrophobicity of the dispersant, and the affinity with the thermoplastic resin can be further improved.
[0080] The (meth)acrylic acid alkyl ester monomer having an alkyl group having 6 to 18 carbon atoms that can be used in the second copolymer is not particularly limited, and examples thereof include cyclohexyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, etc. These (meth)acrylic acid alkyl ester monomers having an alkyl group having 6 to 18 carbon atoms may be used alone or in combination of two or more kinds.
[0081] The acrylic monomer having an amide group that can be used in the second copolymer is not particularly limited, but includes (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-dodecyl acrylamide, N-propoxymethyl acrylamide, 6-(meth)acrylamidohexanoic acid, (meth)acryloylmorpholine, N-methylol(meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-[2,2-dimethyl-3-(dimethylamino)propyl]acrylamide, etc. These acrylic monomers having an amide group may be used alone or in combination of two or more.
[0082] Other monomers that can be used in the second copolymer are not particularly limited, and include the hydrophilic group-containing compound, the glycol ether compound, 2-methylaminoethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, γ-methacryloxypropyltrimethoxylane, vinyltriethoxysilane, glycidyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, etc. These other monomers may be used alone or in combination of two or more.
[0083] Specific examples of the second copolymer include a copolymer of hexyl (meth)acrylate and (meth)acrylamide, a copolymer of hexyl (meth)acrylate and N-methyl (meth)acrylamide, a copolymer of hexyl (meth)acrylate and N,N-dimethyl (meth)acrylamide, a copolymer of 2-ethylhexyl (meth)acrylate and (meth)acrylamide, a copolymer of 2-ethylhexyl (meth)acrylate and N-methyl (meth)acrylamide, a copolymer of 2-ethylhexyl (meth)acrylate and N, Examples of the copolymer include a copolymer with N-dimethyl(meth)acrylamide, a copolymer with lauryl(meth)acrylate and (meth)acrylamide, a copolymer with lauryl(meth)acrylate and N-methyl(meth)acrylamide, a copolymer with lauryl(meth)acrylate and N,N-dimethyl(meth)acrylamide, a copolymer with lauryl(meth)acrylate, (meth)acrylamide and (meth)acrylic acid, a copolymer with lauryl(meth)acrylate, (meth)acrylamide and methyl(meth)acrylate, etc. The second copolymer may be any of a random copolymer, an alternating copolymer, a block copolymer and a graft copolymer, but is preferably a random copolymer or a block copolymer.
[0084] The choline compound is not particularly limited, and examples thereof include 2-(meth)acryloyloxymethyl phosphorylcholine, 2-(meth)acryloyloxyethyl phosphorylcholine, 2-(meth)acryloyloxymethyl phosphorylcholine-methyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-ethyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-propyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-butyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-capryl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-lauryl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-myristyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-stearyl ...propyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-butyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-capryl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-lauryl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-myristyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-stearyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-propyl (meth)acrylate copolymer, 2-(meth)acryloyloxymethyl phosphorylcholine-butyl (meth)acrylate copolymer, 2-(meth)acryloyloxy 2-(meth)acryloyloxymethyl phosphorylcholine-(meth)oleyl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)methyl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)ethyl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)propyl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)butyl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)capryl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)lauryl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)myristyl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)stearyl acrylate copolymer, 2-(meth)acryloyloxyethyl phosphorylcholine-(meth)oleyl acrylate copolymer, and the like.
[0085] Of the above, the dispersant is preferably the first copolymer, the second copolymer, or a choline compound, and more preferably the second copolymer.
[0086] The amount of the dispersant added is preferably 10 to 200 parts by mass, more preferably 20 to 150 parts by mass, and even more preferably 30 to 100 parts by mass, when the total mass of the thermoplastic resin, the cellulose fiber, and the filler is taken as 100 parts by mass. When the amount of the dispersant added is 10 parts by mass or more, the cellulose fiber and the filler can be more finely dispersed, which is preferable. On the other hand, when the amount of the dispersant added is 200 parts by mass or less, the performance deterioration of the composite material due to thermal deterioration and bleed-out can be suppressed, which is preferable.
[0087] [solvent] In one embodiment, the composition may include a solvent.
[0088] The solvent is not particularly limited, but examples thereof include water and organic solvents.
[0089] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, propanol, isopropyl alcohol, and butanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, carbitol acetate, ethyl diglycol acetate, and propylene glycol monomethyl ether acetate; alcohols such as isopropyl alcohol, butanol, cellosolve, and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; and amides such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. Of these, it is preferable to use alcohols and ketones as the organic solvent, and it is more preferable to use butanol, acetone, and methyl ethyl ketone. These organic solvents may be used alone or in combination of two or more.
[0090] The content of the solvent is preferably 1000 parts or less, more preferably 200 parts or less, based on 100 parts of the solid content of the composition. In this specification, the "solid content of the composition" means the total mass of the components in the composition excluding the solvent. Therefore, when the composition does not contain a solvent, the total mass of the composition is the solid content.
[0091] [Additives] In one embodiment, the composition may include an additive.
[0092] The additives are not particularly limited, and examples thereof include defibration aids such as urea, urea derivatives, sugars, sugar alcohols, organic acids, and organic acid salts; decomposition products of the defibration aids; flame retardants such as phosphorus-based flame retardants, nitrogen-based flame retardants, silicone-based flame retardants, inorganic flame retardants, and organic metal salt-based flame retardants; plasticizers; antioxidants; ultraviolet absorbers; light stabilizers; antistatic agents; conductivity imparting agents; stress relaxation agents; release agents; crystallization accelerators; hydrolysis inhibitors; lubricants; impact imparting agents; sliding property improvers; nucleating agents; reinforcing agents; reinforcing agents; flow control agents; dyes; sensitizers; coloring pigments; rubber polymers; thickeners; antisettling agents; antisagging agents; defoamers; coupling agents; rust inhibitors; antibacterial and antifungal agents; antifouling agents; conductive polymers, etc. These additives may be used alone or in combination of two or more.
[0093] <Method of producing the composition> The composition is not particularly limited and can be produced by a known method.
[0094] For example, the composition may be produced by mixing cellulose fibers and a filler and mixing the mixture with a thermoplastic resin, or the composition may be produced by mixing a thermoplastic resin and a filler and mixing the mixture with cellulose fibers, or the composition may be produced by mixing a thermoplastic resin and cellulose fibers and mixing the mixture with a filler, or the composition may be produced by mixing a thermoplastic resin and cellulose fibers, mixing a thermoplastic resin and a filler, and mixing the mixtures prepared separately. In this case, if the cellulose fibers are modified cellulose fibers, the method may further include a step of modifying the cellulose fibers to prepare a cellulose dispersion.
[0095] According to one preferred embodiment, a method for producing the composition includes melt-kneading a mixture comprising a thermoplastic resin, cellulose fibers, and a filler.
[0096] The above-mentioned preferred embodiment will be described in detail below.
[0097] [Mixture] The mixture includes a thermoplastic resin, cellulosic fibers, and a filler.
[0098] (thermoplastic resin) As the thermoplastic resin may be any of those mentioned above, a description thereof will be omitted here.
[0099] The content of the thermoplastic resin in the mixture is preferably 50 to 99% by mass, more preferably 70 to 95% by mass, based on the total mass of the solid content of the mixture. When the amount of the thermoplastic resin added is 50% by mass or more, it is preferable because the obtained composition can be molded into various shapes by heating and melting. On the other hand, when the amount of the thermoplastic resin added is 99% by mass or less, it is preferable because the obtained composition can be given various functions by reinforcing the resin. In this specification, the "solid content of the mixture" means non-volatile components excluding the solvent contained in the mixture. When the mixture does not contain a solvent, the total mass of the mixture is the solid content of the mixture.
[0100] (Cellulose fiber) As the cellulose fibers can be those described above, a description thereof will be omitted here.
[0101] The content of the cellulose fiber raw material in the mixture is preferably 0.1 to 20% by mass, more preferably 0.1 to 10% by mass, based on the total mass of the solid content of the mixture. When the amount of cellulose fiber added is 0.1% by mass or more, the obtained composition can have high mechanical properties, particularly high physical properties (elastic modulus, strength) in the flow direction of the resin (MD direction), which is preferable. On the other hand, when the amount of cellulose fiber added is 20% by mass or less, the melt viscosity of the obtained composition can be reduced, which is preferable because it is easy to handle.
[0102] (Filler) As for the filler, the above-mentioned materials can be used, and therefore the description thereof will be omitted here.
[0103] The content of the filler in the mixture is preferably 2 to 30% by mass, more preferably 5 to 20% by mass, based on the total mass of the solid content of the mixture. When the amount of the filler added is 2% by mass or more, it is preferable because the obtained composition can have high mechanical properties, particularly high physical properties (elastic modulus, strength) in the direction perpendicular to the resin flow (TD direction). On the other hand, when the amount of the filler added is 30% by mass or less, it is preferable because the obtained composition can have high toughness of the composite material.
[0104] (Dispersant) The mixture may contain a dispersant, which allows the cellulose fibers in particular to be suitably dispersed in the thermoplastic resin during melt-kneading, which will be described later.
[0105] As the dispersant, the above-mentioned ones can be used, and therefore the explanation thereof will be omitted here.
[0106] The content of the dispersant in the mixture is preferably 1 to 20% by mass, more preferably 2 to 15% by mass, based on the total mass of the solid content of the mixture. If the dispersant is added at a rate of 1% by mass or more, the cellulose fibers and filler can be more finely dispersed, which is preferable. On the other hand, if the dispersant is added at a rate of 20% by mass or less, the performance deterioration of the composite material due to thermal deterioration and bleed-out can be suppressed, which is preferable.
[0107] (Defibrillating agent) The mixture may contain a defibration aid. When the mixture contains the defibration aid, at least a part of the cellulose fibers can be defibrated during melt kneading, which will be described later. This can result in higher mechanical properties.
[0108] For example, when cellulose fibers having a relatively large width and / or fiber length are used, a defibrating aid can be added to the mixture and the cellulose fibers can be defibrated by utilizing the pressure generated during melt kneading, as described below, to produce cellulose fibers having a small width and / or fiber length, or a composition containing defibrated cellulose fibers.
[0109] Such an advantage is more effective when the cellulose fibers are unmodified. When the cellulose fibers are unmodified, the cellulose fibers have many hydroxyl groups, and therefore are difficult to defibrate due to intramolecular and / or intermolecular hydrogen bonds. For this reason, the unmodified cellulose fibers are usually defibrated in water, dehydrated, dried, and then mixed with a thermoplastic resin. However, according to the present embodiment, the fibers can be defibrated during melt kneading without separately performing steps such as defibration in water, dehydration, and drying. This makes it possible to obtain a composition in which the defibrated unmodified cellulose fibers are suitably dispersed in the thermoplastic resin. Therefore, in a more preferred embodiment, the method for producing the composition includes a step of melt kneading a mixture containing a thermoplastic resin, unmodified cellulose fibers, a filler, and a defibration aid.
[0110] As the defibrating aid can be any of those mentioned above, a description thereof will be omitted here.
[0111] The content of the defibrating aid in the mixture is preferably 0.1 to 10 mass% and more preferably 0.5 to 5 mass% based on the total mass of the solid content of the mixture. When the addition rate of the defibrating aid is 0.1 mass% or more, it is preferable because the cellulose fibers can be defibrated into finer fibers. On the other hand, when the addition rate of the defibrating aid is 10 mass% or less, it is preferable because the deterioration of the mechanical properties of the obtained composition can be suppressed.
[0112] (Solvents, additives) The mixture may further include a solvent and an additive.
[0113] The solvent and additives are the same as those described above, so the explanation is omitted here.
[0114] However, from the viewpoints of production costs, performance of the composition, etc., it is preferable not to use a solvent.
[0115] (Method of preparing the mixture) The method for preparing the mixture is not particularly limited. For example, the mixture may be prepared by mixing the cellulose fiber with a filler and then mixing the mixture with a thermoplastic resin, or the cellulose fiber and the filler may be mixed independently with a thermoplastic resin.
[0116] [Melting and kneading] The composition can be produced by melt-kneading the above-mentioned mixture. If necessary, the composition of the composition can be adjusted by adding a thermoplastic resin, cellulose fiber, filler, etc. during melt-kneading. Since the cellulose fiber can be defibrated during melt-kneading, the cellulose fiber contained in the mixture and the cellulose fiber contained in the resulting composition may differ in width, fiber length, aspect ratio, etc. Furthermore, since force is applied to the filler during melt-kneading, the filler contained in the mixture and the filler contained in the resulting composition may differ in maximum diameter, minimum diameter, aspect ratio, average particle size, etc.
[0117] The melt-kneading temperature varies depending on the thermoplastic resin used, but is preferably from 100 to 380°C, and more preferably from 120 to 280°C.
[0118] The melt-kneading time varies depending on the thermoplastic resin used, but is preferably 1 to 20 minutes, and more preferably 3 to 10 minutes.
[0119] <Molded body> According to one aspect of the present invention, there is provided a molded article, the molded article being obtained by molding the above-mentioned composition.
[0120] In the above-mentioned composition, the cellulose fibers tend to be oriented in the flow direction of the resin (MD direction, etc.), and the filler tends to be oriented in a direction perpendicular to the flow direction of the resin (TD direction, etc.). As a result, the composition has high mechanical properties regardless of the direction. Therefore, the molded article obtained by molding the composition also has high mechanical properties regardless of the direction.
[0121] In one embodiment, the molded body has high mechanical properties against external forces from all directions, and can therefore be suitably applied to interior materials, exterior materials, structural materials, etc. for automobiles, trains, ships, airplanes, etc.; cases, structural materials, internal parts, etc. for personal computers, televisions, watches, telephones, mobile phones, portable music players, video players, printing machines, copying machines, sporting goods, etc.; building materials; office equipment such as stationery, containers, etc.
[0122] <Method of manufacturing molded body> According to one aspect of the present invention, there is provided a method for producing a molded article, the method comprising molding the composition produced by the method described above.
[0123] The method for molding the composition is not particularly limited, but includes compression molding, injection molding, extrusion molding, blow molding, foam molding, etc. These molding methods may be applied alone or in combination of two or more.
[0124] Before or during molding, a thermoplastic resin, cellulose fiber, filler, etc. may be further added to the composition to adjust the physical properties. EXAMPLES
[0125] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.
[0126] [Example 1] (Production of the composition) 80 parts of high density polyethylene (HDPE) as a thermoplastic resin, 4.8 parts of bleached softwood kraft pulp (NBKP) as a cellulose fiber raw material (width: 50 μm, fiber length: 2 mm, manufactured by Howe Sound Pulp and Paper Co.), 15.2 parts of graphite as a filler (aspect ratio: 45, average particle size: 11 μm), and 3 parts of a dispersant were mixed. The resulting mixture was melt-kneaded at 140° C. in a kneading device KZW25 (manufactured by Technobel Co., Ltd.) to produce a composition.
[0127] The width of the cellulose fibers in the obtained composition was measured by the following method. Specifically, the fibers were sandwiched between polyethylene terephthalate sheets and pressed at 160° C. to a thickness of 1 mm, and then the center was cut to 1 cm. 2 The fibers were cut out, wrapped in a metal mesh, and the resin was extracted with hot xylene (heated and refluxed using a mantle heater), after which the cellulose fibers remaining on the wire mesh were dried. The resulting dried cellulose fibers were observed under SEM in the following manner. That is, the fibers were observed at a magnification of 5,000 times, and a straight line was created in which 20 or more cellulose fibers intersected in one field of view. Then, for all cellulose fibers intersecting on the straight line, the distance between the two points on the observation screen that gave the smallest numerical value was measured, and the average value was taken as the width of the cellulose fibers. As a result, the width of the cellulose fibers was 0.7 μm. From this, it can be said that the cellulose fibers in the composition are defibrated NBKP.
[0128] The fiber length of the cellulose fibers in the obtained composition was measured by the following method. Specifically, the composition was sandwiched between polyethylene terephthalate sheets and pressed at 160° C. to a thickness of 1 mm, and then the center was cut by 1 cm. 2 The fibers were cut out, wrapped in a metal mesh, and the resin was extracted with hot xylene, after which the cellulose fibers remaining on the wire mesh were dried. The resulting dried cellulose fibers were then observed using an SEM in the following manner. That is, observations were made at a magnification of 500x, 25 fields of view were synthesized, 20 cellulose fibers with observed start and end points were selected from among them, and the distance between the two points with the largest values was measured, and the average value was taken as the fiber length of the cellulose fibers. As a result, the fiber length of the cellulose fibers was 88 μm.
[0129] The aspect ratio (fiber length / width) of the cellulose fibers in the composition was calculated to be 126.
[0130] The maximum diameter of the filler in the obtained composition was measured by the following method. Specifically, the composition was cut into a size of 1 cm x 1 cm x 0.1 mm, and the obtained sample was observed by SEM by the following method. That is, the observation was performed at a magnification of 5000 times, and 30 fillers present in one field of view were arbitrarily selected, and the maximum diameter of each filler was measured and the average value was calculated. As a result, the maximum diameter of the filler was 4.5 μm.
[0131] Furthermore, the minimum diameter of the filler was observed by SEM using the above sample by the following method. That is, the sample was observed at a magnification of 10,000 times, 30 fillers present in four fields of view were randomly selected, and the minimum diameter of each was measured and the average value was calculated. The result was 0.1 μm.
[0132] The aspect ratio of the filler was calculated by (maximum diameter / minimum diameter), and the resulting aspect ratio was 45.
[0133] (Production of Molded Body) The produced composition was molded into an ISO D2 shape (plate shape) at 160° C. using an injection molding machine, SE-75D (manufactured by Sumitomo Heavy Industries, Ltd.).
[0134] [Example 2] A composition and a molded body were produced in the same manner as in Example 1, except that talc (aspect ratio: 20, average particle size: 5 μm) was used as the filler instead of graphite.
[0135] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.7 μm, 95 μm and 135, respectively.
[0136] Furthermore, the maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 3.6 μm, 0.15 μm and 24, respectively.
[0137] [Example 3] A composition and a molded body were produced in the same manner as in Example 1, except that mica (aspect ratio: 80, average particle size: 25 μm) was used as the filler instead of graphite.
[0138] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.7 μm, 85 μm and 121, respectively.
[0139] Furthermore, the maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 13 μm, 0.15 μm and 86, respectively.
[0140] [Example 4] A composition and a molded body were produced in the same manner as in Example 1, except that the amount of thermoplastic resin added was changed to 73.5 parts, the amount of cellulose fiber raw material added was changed to 10.3 parts, and the amount of filler added was changed to 16.2 parts.
[0141] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.7 μm, 88 μm and 126, respectively.
[0142] Furthermore, the maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 4.5 μm, 0.1 μm and 45, respectively.
[0143] [Example 5] A composition and a molded body were produced in the same manner as in Example 1, except that the amount of thermoplastic resin added was changed to 84.0 parts, the amount of cellulose fiber raw material added was changed to 0.8 parts, and the amount of filler added was changed to 15.1 parts.
[0144] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.7 μm, 89 μm and 127, respectively.
[0145] Furthermore, the maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 4.5 μm, 0.1 μm and 45, respectively.
[0146] [Example 6] A composition and a molded body were produced in the same manner as in Example 1, except that polypropylene (PP) was used as the thermoplastic resin instead of high density polyethylene (HDPE), and the amount of thermoplastic resin added was changed to 84.7 parts, the amount of cellulose fiber raw material added to 5.1 parts, and the amount of filler added to 10.2 parts.
[0147] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.8 μm, 77 μm and 96, respectively.
[0148] Furthermore, the maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 4.5 μm, 0.1 μm and 45, respectively.
[0149] [Example 7] A composition and a molded body were produced in the same manner as in Example 1, except that polyamide (PA) PA6 (manufactured by Ube Industries, Ltd.) was used instead of high density polyethylene (HDPE) as the thermoplastic resin, and the amount of thermoplastic resin added was changed to 84.7 parts, the amount of cellulose fiber raw material added to 5.1 parts, and the amount of filler added to 10.2 parts.
[0150] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.9 μm, 68 μm and 76, respectively.
[0151] Furthermore, the maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 4.5 μm, 0.1 μm and 45, respectively.
[0152] [Comparative Example 1] A composition and a molded article were produced in the same manner as in Example 1, except that the amount of the thermoplastic resin added was 83.3 parts, the amount of the cellulose fiber raw material added was 16.7 parts, and no filler was added.
[0153] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.7 μm, 88 μm and 126, respectively.
[0154] [Comparative Example 2] A composition and a molded article were produced in the same manner as in Example 1, except that the amount of thermoplastic resin added was 84.7 parts, the amount of filler added was 15.3 parts, and no cellulose fiber was added.
[0155] The maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 4.5 μm, 0.1 μm and 45, respectively.
[0156] [Comparative Example 3] A composition and a molded body were produced in the same manner as in Comparative Example 2, except that talc (aspect ratio: 20, average particle size: 5 μm) was used as the filler instead of graphite.
[0157] The maximum diameter, minimum diameter and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 3.6 μm, 0.15 μm and 24, respectively.
[0158] [Comparative Example 4] A composition and a molded body were produced in the same manner as in Comparative Example 2, except that mica (aspect ratio: 80, average particle size: 25 μm) was used as the filler instead of graphite.
[0159] The average particle size and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 13 μm, 0.15 μm and 86, respectively.
[0160] [Comparative Example 5] A composition and a molded body were produced in the same manner as in Example 1, except that talc (aspect ratio: 5, average particle size: 5 μm) was used as the filler instead of graphite.
[0161] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.7 μm, 86 μm and 125, respectively.
[0162] The average particle size, minimum particle size and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.8 μm, 0.16 μm and 5, respectively.
[0163] [Comparative Example 6] A composition and a molded body were produced in the same manner as in Example 1, except that, as the cellulose fiber raw material, hardwood bleached kraft pulp (LBKP) (width: 50 μm, fiber length: 0.8 mm, manufactured by Howe Sound Pulp and Paper) was used instead of softwood bleached kraft pulp (NBKP), and as the filler, talc (aspect ratio: 20, average particle size: 5 μm) was used instead of graphite, and the amount of thermoplastic resin added was changed to 78.1 parts, the amount of cellulose fiber raw material added to 7.8 parts, and the amount of filler added to 14.1 parts.
[0164] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 1.5 μm, 30 μm and 20, respectively.
[0165] The average particle size, minimum particle size and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 3.6 μm, 0.15 μm and 24, respectively.
[0166] [Comparative Example 7] A composition and a molded article were produced in the same manner as in Comparative Example 1, except that polypropylene (PP) was used as the thermoplastic resin instead of high density polyethylene (HDPE).
[0167] The width, fiber length and aspect ratio of the cellulose fibers in the composition were measured and calculated in the same manner as in Example 1, and were found to be 0.7 μm, 98 μm and 140, respectively.
[0168] [Comparative Example 8] A composition and a molded article were produced in the same manner as in Comparative Example 3, except that polypropylene (PP) was used as the thermoplastic resin instead of high density polyethylene (HDPE).
[0169] The average particle size, minimum particle size and aspect ratio of the filler in the composition were measured and calculated in the same manner as in Example 1, and were found to be 3.6 μm, 0.15 μm and 24, respectively.
[0170] The compositions produced in Examples 1 to 7 and Comparative Examples 1 to 8 are shown in Table 1 below.
[0171] [Table 1]
[0172] [Physical property evaluation] The compositions and molded articles produced in Examples 1 to 7 and Comparative Examples 1 to 8 were evaluated for various physical properties.
[0173] (Melt Flow Rate (MFR)) 5 g of the composition produced was put into a cylinder and heated to a predetermined temperature. Then, under a load of 2.16 kgf, the resin extruded from the die (diameter (maximum diameter): 2 mm) at the bottom of the cylinder was manually cut twice every minute. The amount of resin per 10 minutes was calculated, and the average value was calculated and evaluated according to the following criteria. The results are shown in Table 2 below.
[0174] In addition, the predetermined temperature is 190°C for Examples 1 to 6 and Comparative Examples 1 to 8, and 230°C for Example 7.
[0175] ○: 4g / 10 minutes or more △: 1g / 10min or more and less than 4g / 10min ×: Less than 1g / 10 minutes
[0176] (MD bending modulus) The produced molded product was cut in the MD direction to a width of 25 mm to prepare a MD test piece. The obtained test piece was used to measure the MD bending modulus by a bending test according to ISO 178. The obtained bending modulus was evaluated according to the following criteria. The obtained results are shown in Table 2 below.
[0177] ○: Flexural modulus in MD direction is 2.5 GPa or more △: Flexural modulus in the MD direction is 2.0 GPa or more and less than 2.5 GPa ×: Flexural modulus in MD direction is less than 2.0 GPa
[0178] (TD flexural modulus) The produced molded body was cut out in the TD direction to a width of 25 mm to prepare a TD direction test piece. The obtained test piece was used to measure the flexural modulus in the TD direction by a bending test according to ISO 178. The obtained flexural modulus was evaluated according to the following criteria. The obtained results are shown in Table 2 below.
[0179] ○: Flexural modulus in TD direction is 2.5 GPa or more △: Flexural modulus in the TD direction is 2.0 GPa or more and less than 2.5 GPa ×: Flexural modulus in TD direction is less than 2.0 GPa
[0180] (MD / TD elastic modulus ratio) The measured value of MD bending elasticity was divided by the measured value of TD bending elasticity (MD bending elasticity / TD bending elasticity) to calculate the MD / TD elasticity ratio, which was evaluated according to the following criteria. The obtained results are shown in Table 2 below.
[0181] ○: MD / TD elastic modulus ratio is 0.9 to 1.1 ×: MD / TD elastic modulus ratio is less than 0.9 or more than 1.1
[0182] (MD / TD intensity ratio) The strength in the MD direction (MD strength) and the strength in the TD direction (TD strength) were measured using the above MD and TD test pieces by bending tests according to ISO 178. The measured value of the MD strength was divided by the measured value of the TD strength (MD strength / TD strength) to calculate the MD / TD strength ratio, which was evaluated according to the following criteria. The results are shown in Table 2 below.
[0183] ○: MD / TD strength ratio is 0.9 to 1.0 ×: MD / TD strength ratio is less than 0.9 or more than 1.0
[0184] (Specific elastic modulus) The specific gravity was measured by the Archimedes method using the above MD test piece.The specific elastic modulus was calculated by dividing the MD bending elastic modulus by the specific gravity (MD bending elastic modulus / specific gravity), and was evaluated according to the following criteria.The results are shown in Table 2 below.
[0185] ○: Specific elastic modulus is 2.5 GPa or more △: Specific elastic modulus is 2.0GPa or more and less than 2.5GPa ×: Specific elastic modulus is less than 2.0 GPa
[0186] (specific strength) The specific gravity was measured by Archimedes' method using the above MD test piece. The measured value of strength in MD was divided by specific gravity (strength in MD / specific gravity) to calculate the specific elastic modulus, which was evaluated according to the following criteria. The results are shown in Table 2 below.
[0187] ○: Specific strength is 40N·m / kg or more △: Specific strength is 30N·m / kg or more and less than 40N·m / kg ×: Specific strength is less than 30N·m / kg
[0188] [Table 2]
[0189] Comparing Examples 1 to 7 with Comparative Examples 1 to 8, it is found that Examples 1 to 7 have excellent flexural modulus in both MD and TD, and the modulus ratios are at the same level, i.e., Examples 1 to 7 have high mechanical properties regardless of directionality.
[0190] In addition, for Comparative Example 5, both the MD bending elastic modulus and the TD bending elastic modulus were rated as "△", but when the MD / TD elastic modulus ratio was calculated using the measured values, the evaluation result was "×".
Claims
1. The composite material is produced by melt-kneading a mixture containing a thermoplastic resin, cellulose fibers, and a filler, A composition comprising a thermoplastic resin, cellulose fibers having an aspect ratio of 100 to 20,000 after kneading, and a filler having an aspect ratio of 10 to 75 after kneading, The composition, wherein the filler having an aspect ratio of 10 to 75 after kneading is a resin particle, an aramid fiber or an inorganic filler.
2. The composition according to claim 1 , wherein the maximum diameter of the filler is 50 μm or less.
3. The composition according to claim 1 or 2, wherein the content of the cellulose fiber is 0.1 to 20% by mass based on the total mass of the thermoplastic resin, the cellulose fiber, and the filler.
4. A molded article obtained by molding the composition according to any one of claims 1 to 3.
5. A method for producing the composition according to any one of claims 1 to 3, comprising the steps of: The method includes melt-kneading a mixture containing the thermoplastic resin, the cellulose fibers, and the filler.
6. A method for producing a molded article, further comprising the step of molding the composition produced by the method of claim 5.
Citation Information
Patent Citations
Composite composition
JP2010285573A
Polyamide resin composition and method of producing polyamide resin composition
JP2013079333A
Cellulose fiber-containing resin composition
JP2014015512A
Composite resin composition
JP2018115254A
Composite resin molding
JP2019085529A